Stability Indicating Reverse Phase-High Performance Liquid Chromatography Method for Simultaneous Estimation of Cabotegravir and Rilpivirine - Vemuluri, Padmabhushana Chary; Dodda, Sireesha (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: For the estimation of cabotegravir and rilpivirine in the bulk and pharmaceutical dosage form, a stability-indicating reverse-phase high-performance liquid chromatography method was developed and validated using an inertsil C18 (150 x 4.6 mm, 5 µm) column. At a flow rate of 1.0 ml/min, a mobile phase containing a mixture of 0.01N ammonium acetate buffer (pH 3) and acetonitrile (65:35, v/v) was passed over the column. The column temperature was set at 30°C. A photodiode array detector was used at the wavelength of 257 nm. Results: Retention times of cabotegravir and rilpivirine were found to be 2.250 min and 2.823 min, respectively. The calibration curves were linear over the concentration range of 10-60 µg/ml and 15-90 µg/ml for cabotegravir and rilpivirine, respectively with a correlation coefficient (R2) of 0.999. The percent relative standard deviation (% RSD) for precision and robustness studies was found to be < 2%. The mean % recovery was obtained as 100.71 % and 100.01 % for cabotegravir and rilpivirine, respectively. The degradation during stability studies was more in the presence of oxidative conditions. Conclusion: The developed method was found to be simple, rapid, and economical and can be applied successfully for simultaneous estimation of cabotegravir and rilpivirine in regular analysis.
Keywords: Cabotegravir; Rilpivirine; RP-HPLC; Method Validation; Stability studies